A pn heterojunction photocathode material and preparation method thereof
By loading the SnS2 film layer on the surface of the Cu2O film layer and supporting the NiCoSex catalyst on the surface of the perfluorosulfonic acid polymer film layer, the p-n heterojunction photocathode material with a layered structure is solved in the prior art. The low efficiency of photoelectric catalytic hydrogen production and unstable Cu2O have achieved efficient and stable photoelectric catalytic hydrogen evolution effect and saved costs.
Patent Information
- Application Number
- CN202211039816.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-08-29
AI Technical Summary
The existing p-n heterojunction materials have extremely low efficiency in photoelectro-catalyzed hydrogen production, and Cu2O is extremely unstable.
A p-n heterojunction photocathode material with a layered structure is adopted, including a base layer, an Au layer, a Cu2O film layer, a SnS2 film layer and a perfluorosulfonic acid polymer film layer, which is surface-supported hydrogen evolution catalyst NiCoSex. By loading the SnS2 film layer on the surface of the Cu2O film layer, a heterojunction is formed, which promotes the separation of photogenerated electron-holes, and improves the efficiency of photoelectrocatalytic hydrogen evolution through the perfluorosulfonic acid polymer film layer and NiCoSex catalyst.
The efficiency of photoelectro-catalytic hydrogen evolution is improved, the photogenerated electron-hole recombination rate is reduced, the stability of the electrode is enhanced, and the cost is saved, avoiding the use of expensive ALD equipment.
Smart Images

Figure CN115354343B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of semiconductor materials, and in particular to a pn heterojunction photocathode material and a preparation method thereof. Background Art
[0002] Cu 2 CuO is a relatively new type of p-type oxide, and it is cheaper than common semiconductor cathode materials such as p-Si, and can be used as the cathode material of the photoelectrocatalytic reaction system. 2 The synthesis methods of O are relatively mature and have been systematically studied. Common methods include reactive sputtering, thermal oxidation, electrodeposition and metal organic chemical vapor deposition (ALD), but the common methods have the problem of unstable product quality, especially in the photoelectrocatalytic system, Cu 2 O is tested directly under light conditions, and its chemical properties are extremely unstable, so the single Cu 2 O cannot be used as a photocathode, and its surface must be protected. The commonly used method is to design a pn heterostructure. 2 O is a p-type material, and another n-type material that matches its energy band is selected (common ones such as TiO 2 , Al-doped ZnO, etc.). On the one hand, the PN structure can promote the separation of photogenerated electrons and holes and improve the photoelectric conversion efficiency. On the other hand, Cu 2 O is protected from direct contact with light and electrolyte, and its stability is greatly improved.
[0003] Currently based on Cu 2 There are many literature reports on the pn heterojunction structure of O. It can be roughly divided into three categories: (1) Planar heterojunction, choose a suitable substrate material, such as Cu sheet, Al sheet, ITO, FTO, etc. Usually in order to improve the subsequent Cu 2 The adhesion of O thin film on ITO and FTO conductive glass is to pre-plate a layer of Au or other metal with a thickness of about 100-200nm on the surface of ITO or FTO. Cu is grown on the surface of the substrate by electrochemical deposition or other chemical methods. 2 O thin film, and based on this, continue to use sputtering or atomic deposition (ALD) method to deposit Cu 2 O surface to grow Al-doped ZnO (AZO) and (or) TiO 2 In order to improve the catalytic effect, common precious metal catalysts Pt, RuO 2 , or transition metal-based catalysts such as CoSx; (2) three-dimensional heterostructures, growing Cu on a copper substrate 2 O nanowires or depositing Cu on other three-dimensional substrates 2O thin film, and then grow other n-type oxides on the surface of the three-dimensional nanowire array, and finally load or not load the catalyst; (3) pure Cu 2 Preparation of O, and research on its photoelectric properties or sensing properties.
[0004] However, the photoelectrocatalytic hydrogen production efficiency of existing pn heterojunction materials is extremely low, and Cu 2 O is extremely unstable. Summary of the invention
[0005] In order to solve the problems of the prior art, the present invention provides a pn heterojunction photocathode material and a preparation method thereof.
[0006] In one aspect, a pn heterojunction photocathode material is provided, wherein the photocathode material is layered and includes: a substrate layer;
[0007] The base layer is provided with Au layer, Cu layer, 2 O thin film layer, SnS 2 A film layer and a perfluorosulfonic acid polymer film layer;
[0008] The surface of the perfluorosulfonic acid polymer film layer is loaded with a hydrogen evolution catalyst;
[0009] The hydrogen evolution catalyst is NiCoSe x .
[0010] Furthermore, the thickness of the Au layer is 100 to 200 mm;
[0011] The Cu 2 The thickness of the O film layer is 1.5 to 2.5 μm;
[0012] The base layer is an ITO conductive glass layer;
[0013] The Cu 2 In the O thin film layer, Cu 2 The microscopic crystal morphology of O is cubic crystal, and the Cu 2 The O film layer as a whole is a dense and uneven micro-nanocone array film.
[0014] In another aspect, a method for preparing a pn heterojunction photocathode material is provided, the method comprising:
[0015] Plating an Au layer on the surface of the substrate layer to obtain a substrate layer / Au material;
[0016] Cu is grown on the surface of the Au layer. 2 O thin film layer, to obtain the base layer / Au / Cu 2 OMaterial;
[0017] In the Cu 2 SnS is loaded on the surface of O thin film layer 2 Thin film layer, get base layer / Au / Cu 2 O / SnS 2 Material;
[0018] In the SnS 2 The surface of the film layer is spin-coated with a hydrogen evolution catalyst NiCoSe x The perfluorosulfonic acid polymer thin film layer is formed to obtain the pn heterojunction photocathode material.
[0019] Further, Cu is grown on the surface of the Au layer. 2 O thin film layer methods include:
[0020] The base layer coated with the Au layer is used as a working electrode, the working electrode is immersed in an electrolyte, a high-purity carbon rod is used as a counter electrode, Hg / HgO is used as a reference electrode, and the Cu is grown on the surface of the Au layer by electrodeposition. 2 O thin film layer, to obtain the base layer / Au / Cu 2 OMaterial.
[0021] Furthermore, the electrodeposition conditions are:
[0022] The electrodeposition current density is -0.1~-0.2mA / cm 2 , the electrodeposition time is 1-6 hours, and the electrodeposition temperature is 30-50°C;
[0023] The components of the electrodeposition electrolyte at least include: 0.8-1.2 mol / L of copper sulfate pentahydrate, 0.4-0.6 mol / L of sodium lactate, and 0.08-0.12 mol / L of Triton X-1000;
[0024] The electrodeposition electrolyte also includes a surfactant, and the amount of the surfactant added is 0.8-1.2% of the volume of the electrodeposition electrolyte;
[0025] The surfactant is polyethylene glycol PEG-200;
[0026] The pH of the electrodeposition electrolyte is 11 to 12;
[0027] The electrodeposition electrolyte also includes a pH regulator, which is an alkaline substance;
[0028] The alkaline substance is selected from at least one of NaOH and KOH.
[0029] Furthermore, in the Cu 2 SnS is loaded on the surface of O thin film layer 2 Thin film layer methods include:
[0030] SnS 2 The nanoparticles are ground and ultrasonically dispersed in solvent A to obtain an impregnation solution, wherein Triton X-100 is added to the solvent A.
[0031] The base layer / Au / Cu was prepared by immersion pulling method. 2 O material is immersed in the impregnation solution, and the Cu 2 SnS is loaded on the surface of O thin film layer 2 The thin film layer is dried after loading to obtain the base layer / Au / Cu 2 O / SnS 2 Material.
[0032] Furthermore, in the impregnation solution, the volume of Triton X-100 is 1-2% of the volume of the solvent A; 2 The mass volume ratio of the nanoparticles to the solvent A is 1:2-3;
[0033] The solvent A is selected from at least one of ethanol and isopropanol;
[0034] The conditions of the immersion pulling method are: the immersion time is 30-120s, the pulling times are 5-20 times, and the interval time between each time is 250-350s;
[0035] The drying conditions are as follows: drying temperature is 35-45° C., and drying time is 5-7 hours.
[0036] Furthermore, in the SnS 2 The surface of the film layer is spin-coated with a hydrogen evolution catalyst NiCoSe x The method of forming a perfluorosulfonic acid polymer film layer comprises:
[0037] Containing NiCoSe x The solution is mixed with the solution containing Nafion to obtain Nafion and NiCoSe x Mixed liquid,
[0038] The Nafion and NiCoSe x After ultrasonic dispersion of the mixed solution, it was spin-coated on the substrate / Au / Cu 2 O / SnS 2 SnS of materials 2 The surface of the thin film layer is dried to obtain the pn heterojunction photocathode material.
[0039] Furthermore, the NiCoSe x The solution further includes a solvent B, wherein the solvent B is a mixture of water and isopropanol,
[0040] The volume ratio of the water to the isopropanol is 4-2:1;
[0041] The NiCoSe x NiCoSe in solution x The mass ratio of the Nafion-containing solution to the isopropanol is 1:200-400, the mass fraction of Nafion in the Nafion-containing solution is 5%, and the volume ratio of the Nafion-containing solution to the isopropanol is 0.05:1.
[0042] Furthermore, the drying conditions are: drying temperature is 35-45° C., and drying time is 1-3 hours.
[0043] The technical solution provided by the embodiment of the present invention has the following beneficial effects: the pn heterojunction photocathode material in the present invention comprises: a base layer, on which Au layer, Cu layer and Cu layer are sequentially attached from bottom to top; 2 O thin film layer, SnS 2 The surface of the perfluorosulfonic acid polymer film layer is loaded with a hydrogen evolution catalyst NiCoSe x , through Cu 2 SnS is loaded on the surface of O thin film layer 2 The thin film layer makes Cu 2 O and SnS 2 The formation of a heterojunction is beneficial to the separation of photogenerated electrons and holes, increasing the open circuit voltage, and 2 Stable and dense perfluorosulfonic acid polymer film layer is formed on the surface and high-efficiency hydrogen evolution catalyst NiCoSe is loaded x , which helps to reduce the recombination rate of photogenerated electrons and holes, improve the efficiency of photoelectrocatalytic hydrogen evolution, and protect the electrodes to improve stability.
[0044] In addition, the ALD (atomic layer deposition) method is used in the prior art to deposit Cu 2 The surface of O is loaded with ZnO, or ZnO doped with Al, i.e., AZO. In the present invention, ZnO or AZO is replaced by SnS 2 Instead, the immersion pulling method is used, which does not require expensive ALD equipment and saves costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0046] Figure 1It is a schematic structural diagram of a pn heterojunction photocathode material provided by the present invention;
[0047] Figure 2 This invention provides an ITO / Au / Cu 2 O / SnS 2 SEM image of the cross section of the electrode heterojunction;
[0048] Figure 3 The present invention provides a Cu electrodeposition time of different 2 O surface morphology;
[0049] Figure 4 The present invention provides an electrodeposited Cu 2 XRD pattern of O;
[0050] Figure 5 The present invention provides an ITO / Au / Cu electrodeposition method with different electrodeposition times. 2 O electrode photoelectrocatalytic hydrogen evolution performance data diagram;
[0051] Figure 6 This invention provides an ITO / Au / Cu 2 O electrode stability test current variation over time;
[0052] Figure 7 This invention provides an ITO / Au / Cu 2 O / SnS 2 SEM images of electrodes;
[0053] Figure 8 This invention provides an ITO / Au / Cu 2 O / SnS 2 Photoelectrocatalytic performance test diagram of electrode samples with different pulling times;
[0054] Fig. 9 This invention provides an ITO / Au / Cu 2 O / SnS 2 / Nafion / NiCoSe x SEM images of electrodes;
[0055] Fig.10 This invention provides an ITO / Au / Cu 2 O / SnS 2 / Nafion / NiCoSe x Electrode and ITO / Au / Cu 2 O / SnS 2 / Photoelectric performance test comparison chart of Pt electrode;
[0056] Fig.11 This invention provides an ITO / Au / Cu 2 O / SnS 2 / Nafion / NiCoSe x Electrode constant potential stability test diagram;
[0057] Fig.12 This invention provides an ITO / Au / Cu 2 O / SnS 2 / Nafion / NiCoSe x Electrode stability test diagram;
[0058] Fig.13 It is a component analysis diagram provided by the present invention;
[0059] Fig.14 This invention provides an ITO / Au / Cu 2 Cross-sectional scanning photo of O electrode. DETAILED DESCRIPTION
[0060] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.
[0061] Embodiment 1
[0062] A method for preparing a pn heterojunction photocathode material specifically comprises the following steps:
[0063] Step (101): Select an ITO conductive glass layer as the base substrate layer, and use a high vacuum composite sputtering coating system to plate an Au layer on the surface of the ITO conductive glass layer, with an RF power of 500 W, a DC power of 700 W, and a studio vacuum of 6.7×10 -5 Pa, Au layer deposition thickness 100nm, ITO / Au electrode. Plating a layer of Au on ITO conductive glass can prevent Cu 2 O is easy to fall off. Wherein, the base layer can also be FTO.
[0064] Step (102): Using an ITO conductive glass layer coated with an Au layer as a working electrode, the ITO conductive glass layer is 1 cm×5 cm, and the depth of immersion in the electrolyte is at least 1 cm, using a high-purity carbon rod as a counter electrode, and the reference electrode is Hg / HgO, and growing Cu on the surface of the Au layer by electrodeposition 2 O thin film layer, constant current deposition, current density is -0.1mA / cm 2 The electroplating time was 1 hour. During the electroplating process, the electrolytic cell was heated at a constant temperature of 30°C to obtain ITO / Au / Cu 2 O electrode, Cu 2The thickness of the O film layer is 1.5 μm, and the Cu 2 O is a cubic crystal, Cu 2 The O film layer as a whole appears as a dense and uneven micro-nanocone array film.
[0065] The components of the electrodeposition electrolyte include at least: 0.8 mol / L copper sulfate pentahydrate, 0.4 mol / L sodium lactate, and 0.08 mol / L Triton X-100. The electrodeposition electrolyte also includes a surfactant polyethylene glycol PEG-200, and the amount of polyethylene glycol PEG-200 added is 0.8% of the volume of the electrodeposition electrolyte. NaOH is added to adjust the pH of the electrolyte to 11.
[0066] Step (103): Preparation of SnS 2 Nanoparticles: Dissolve 10 mmol of thiourea in 50 ml of ethylene glycol, control the temperature of the electromagnetic stirrer heating plate to 120 °C, wait until the thiourea is fully dissolved and heated evenly, and then add 50 mL of 2 mmol / L SnCl 4 The ethylene glycol solution was slowly dripped into the above thiourea solution using a separatory funnel, and the dripping rate was controlled to 1 drop / second. The entire operation was carried out in a fume hood with personal protection. After sufficient reaction for 10 hours, the yellow product was collected by centrifugation, and washed alternately with ethylene glycol and ultrapure water for 3 times, and dried in a vacuum at 50°C for 12 hours.
[0067] Step (104): SnS 2 Nanoparticle grinding, ultrasonic dispersion in ethanol solvent, SnS 2 The mass volume ratio of nanoparticles to ethanol solvent was 1:2. To improve the dispersibility of nanoparticles, 1% volume fraction of Triton X-100 was added to the ethanol solvent to obtain an impregnation solution. The ITO / Au / Cu 2 The O electrode was immersed in the impregnation solution for 30 seconds, and the pulling times were 5 times, with an interval of 250 seconds between each coating. After the coating was completed, the electrode was placed in a vacuum drying oven at 35°C for 5 hours to obtain ITO / Au / Cu 2 O / SnS 2 electrode.
[0068] Step (105): Preparation of NiCoSe x ,NiCoSe x The preparation was carried out in a three-electrode system, with blank ITO conductive glass as the working electrode, saturated calomel electrode as the reference electrode, Pt sheet as the counter electrode (1 cm × 1 cm), and the electrolyte stock solution was 10 mM CoCl 2 6H 2 O, 10 mM NiCl 2 6H2 O, 10 mM SeO 2 The electrolyte stock solution was diluted in a ratio of 1:6, that is, 1 volume of electrolyte stock solution and 6 volumes of ultrapure water were used as the electrolyte for electrodeposition. The electrolyte was continuously exposed to high-purity N for 30 minutes before use and during use. 2 To remove dissolved oxygen in the system, the electrodeposition potential was -0.7 V (vs SCE) and the electrodeposition time was 30 min. After the deposition was completed, the NiCoSe x Peel off the ITO conductive glass surface to obtain NiCoSe x .
[0069] It should be noted that NiCoSe x The X in the figure indicates that the catalyst is an amorphous material. The three elements Ni, Co, and Se do not have a definite ratio or specific crystal form. Fig.13 , NiCoSe was analyzed by X-ray energy dispersive spectrometer (EDS) x The material composition analysis shows that the catalyst ternary distribution ratio in the present invention is Ni 1.3 CoSe 2 .
[0070] Step (106): NiCoSe x Grind and weigh 5 mg of ground NiCoSe x , added to a mixture of 1.3 ml isopropanol and 5.2 ml water to obtain a solution containing NiCoSe x The solution was added with 65 μl of a solution containing 5% Nafion by mass to obtain Nafion and NiCoSe x Mixed solution, wherein Nafion solution is DuPont, model: D520, water content: 45±3%, volatile organic matter content: 50±3%, exchange capacity: 1.03-1.12, resin solid content: 5%, Nafion and NiCoSe x After the mixed solution was ultrasonically dispersed, it was spin-coated on ITO / Au / Cu 2 O / SnS 2 SnS electrode 2 The surface of the film layer is spin-coated with a hydrogen evolution catalyst NiCoSe x The spin coater was operated at a speed of 2000 rpm to obtain ITO / Au / Cu 2 O / SnS 2 / Nafion / NiCoSe x Electrode, ITO / Au / Cu 2 O / SnS 2 / Nafion / NiCoSe x The electrode was dried in a vacuum oven at 35° C. for 1 hour to obtain a pn heterojunction photocathode material.
[0071] Step (107): The photocathode material is packaged before the photoelectrocatalysis is performed. The packaging is performed by coating the outer edge of the photocathode material with epoxy resin AB glue to prevent the edge Cu 2 O is in contact with the electrolyte.
[0072] Embodiment 2
[0073] A method for preparing a pn heterojunction photocathode material specifically comprises the following steps:
[0074] Step (201): Select an ITO conductive glass layer as the base substrate layer, and use a high vacuum composite sputtering coating system to plate an Au layer on the surface of the ITO conductive glass layer. The Au layer deposition thickness is 150nm. The specific parameters of the equipment during coating are the same as those in Example 1.
[0075] Step (202): Using an ITO conductive glass layer coated with an Au layer as a working electrode, the ITO conductive glass layer is 1 cm×5 cm, and the depth of immersion in the electrolyte is at least 1 cm, using a high-purity carbon rod as a counter electrode, and the reference electrode is Hg / HgO, and growing Cu on the surface of the Au layer by electrodeposition 2 O thin film layer, constant current deposition, current density is -0.15mA / cm 2 The electroplating time is 2 hours. During the electroplating process, the electrolytic cell is heated at a constant temperature of 40°C to obtain ITO / Au / Cu 2 O electrode, Cu 2 The thickness of the O film layer is 2 μm, and the Cu 2 O is a cubic crystal, Cu 2 The O film layer as a whole appears as a dense and uneven micro-nanocone array film.
[0076] The components of the electroplating electrolyte include: 1 mol / L copper sulfate pentahydrate, 0.5 mol / L sodium lactate, and 0.1 mol / L Triton X-100. The electroplating electrolyte also includes a surfactant polyethylene glycol PEG-200, and the amount of polyethylene glycol PEG-200 added is 1% of the volume of the electroplating electrolyte. KOH is added to adjust the pH of the electrolyte to 12.
[0077] Step (203): Preparation of SnS 2 Nanoparticles are the same as those in Example 1.
[0078] Step (204): SnS 2 Nanoparticles were ground and ultrasonically dispersed in isopropanol solvent. SnS 2The mass volume ratio of nanoparticles to isopropanol solvent was 1:2. To improve the dispersibility of nanoparticles, 1.5% volume fraction of Triton X-100 was added to the isopropanol solvent to obtain an impregnation solution. The ITO / Au / Cu 2 The O electrode was immersed in the impregnation solution for 80 seconds, and the pulling times were 10 times. The interval between each coating was 300 seconds. After the coating was completed, the electrode was placed in a vacuum drying oven at 40°C for 6 hours to obtain ITO / Au / Cu 2 O / SnS 2 electrode.
[0079] Step (205): Preparation of NiCoSe x , the same as in Example 1.
[0080] Step (206): NiCoSe x Grind and weigh 5 mg of ground NiCoSe x , added to a mixture of 2 ml isopropanol and 6 ml water to obtain a mixture containing NiCoSe x The solution was mixed with 100 μl of Nafion solution containing 5% Nafion by mass to obtain Nafion and NiCoSe x Mix the Nafion and NiCoSe x After the mixed solution was ultrasonically dispersed, it was spin-coated on ITO / Au / Cu 2 O / SnS 2 SnS electrode 2 The surface of the film layer is spin-coated with a hydrogen evolution catalyst NiCoSe x The spin coater was operated at a speed of 2000 rpm to obtain ITO / Au / Cu 2 O / SnS 2 / Nafion / NiCoSe x Electrode, ITO / Au / Cu 2 O / SnS 2 / Nafion / NiCoSe x The electrode was dried in a vacuum oven at 40° C. for 2 hours to obtain a pn heterojunction photocathode material.
[0081] Step (207): The photocathode material is packaged before the photoelectrocatalysis is performed. The packaging is performed by coating the outer edge of the photocathode material with epoxy resin AB glue to prevent the edge Cu 2 O is in contact with the electrolyte.
[0082] Embodiment 3
[0083] A method for preparing a pn heterojunction photocathode material specifically comprises the following steps:
[0084] Step (301): Select an ITO conductive glass layer as a base substrate, and use a high vacuum composite sputtering coating system to plate an Au layer on the surface of the ITO conductive glass layer. The Au layer deposition thickness is 150nm. The specific parameters of the equipment during coating are the same as those in Example 1.
[0085] Step (302): Using an ITO conductive glass layer coated with an Au layer as a working electrode, the ITO conductive glass layer is 1 cm×5 cm, and the depth of immersion in the electrolyte is at least 1 cm, using a high-purity carbon rod as a counter electrode, and the reference electrode is Hg / HgO, and growing Cu on the surface of the Au layer by electrodeposition 2 O thin film layer, constant current deposition, current density is -0.1mA / cm 2 The electroplating time was 3 hours. During the electroplating process, the electrolytic cell was heated at a constant temperature of 30°C to obtain ITO / Au / Cu 2 O electrode, Cu 2 The thickness of the O film layer is 2.3 μm, and the Cu 2 O is a cubic crystal, Cu 2 The O film layer as a whole appears as a dense and uneven micro-nanocone array film.
[0086] The components of the electroplating electrolyte include: 1 mol / L copper sulfate pentahydrate, 0.5 mol / L sodium lactate, and 0.1 mol / L Triton X-100. The electroplating electrolyte also includes a surfactant polyethylene glycol PEG-200, and the amount of polyethylene glycol PEG-200 added is 1% of the volume of the electroplating electrolyte. NaOH is added to adjust the pH of the electrolyte to 12.
[0087] Step (303): Preparation of SnS 2 Nanoparticles are the same as those in Example 1.
[0088] Step (304): SnS 2 Nanoparticle grinding, ultrasonic dispersion in ethanol solvent, SnS 2 The mass volume ratio of nanoparticles to ethanol solvent was 1:2.5. To improve the dispersibility of nanoparticles, 1.5% volume fraction of Triton X-100 was added to the ethanol solvent to obtain an impregnation solution. The ITO / Au / Cu 2 The O electrode was immersed in the impregnation solution for 80 seconds, and the pulling times were 15 times. The interval between each coating was 300 seconds. After the coating was completed, the electrode was placed in a vacuum drying oven at 40°C for 6 hours to obtain ITO / Au / Cu 2 O / SnS 2 electrode.
[0089] Step (305): Preparation of NiCoSe x , the same as in Example 1.
[0090] Step (306): NiCoSe x Grind and weigh 5 mg of ground NiCoSe x , added to a mixture of 2 ml isopropanol and 6 ml water to obtain a mixture containing NiCoSe x The solution was mixed with 100 μl of Nafion solution (5% by mass) to obtain Nafion and NiCoSe. x Mix the Nafion and NiCoSe x After the mixed solution was ultrasonically dispersed, it was spin-coated on ITO / Au / Cu 2 O / SnS 2 SnS electrode 2 The surface of the film layer is spin-coated with a hydrogen evolution catalyst NiCoSe x The spin coater was operated at a speed of 2000 rpm to obtain ITO / Au / Cu 2 O / SnS 2 / Nafion / NiCoSe x Electrode, ITO / Au / Cu 2 O / SnS 2 / Nafion / NiCoSe x The electrode was dried in a vacuum oven at 40° C. for 2 hours to obtain a pn heterojunction photocathode material.
[0091] Step (307): The photocathode material is packaged before the photoelectrocatalysis is performed. The packaging is performed by coating the outer edge of the photocathode material with epoxy resin AB glue to prevent the edge Cu 2 O is in contact with the electrolyte.
[0092] Embodiment 4
[0093] A method for preparing a pn heterojunction photocathode material specifically comprises the following steps:
[0094] Step (401): Select an ITO conductive glass layer as a base substrate, and use a high vacuum composite sputtering coating system to plate an Au layer on the surface of the ITO conductive glass layer. The Au layer deposition thickness is 200nm. The specific parameters of the equipment during coating are the same as those in Example 1.
[0095] Step (402): Using an ITO conductive glass layer coated with an Au layer as a working electrode, the ITO conductive glass layer is 1 cm×5 cm, and the depth of immersion in the electrolyte is at least 1 cm, using a high-purity carbon rod as a counter electrode, and the reference electrode is Hg / HgO, and growing Cu on the surface of the Au layer by electrodeposition 2 O thin film layer, constant current deposition, current density is -0.2mA / cm 2 The electroplating time is 6 hours. During the electroplating process, the electrolytic cell is heated at a constant temperature of 50°C to obtain ITO / Au / Cu 2 O electrode, Cu 2 The thickness of the O thin film layer is 2.5 μm.
[0096] The components of the electroplating electrolyte include: 1.2 mol / L copper sulfate pentahydrate, 0.56 mol / L sodium lactate, and 0.12 mol / L Triton X-100. The electroplating electrolyte also includes a surfactant, polyethylene glycol PEG-200, the amount of polyethylene glycol PEG-200 added is 1.2% of the volume of the electroplating electrolyte, and KOH is added to adjust the pH of the electrolyte to 12.
[0097] Step (403): Preparation of SnS 2 Nanoparticles are the same as those in Example 1.
[0098] Step (404): SnS 2 Nanoparticles were ground and ultrasonically dispersed in isopropanol solvent. SnS 2 The mass volume ratio of nanoparticles to isopropanol solvent was 1:3. To improve the dispersibility of nanoparticles, 2% volume fraction of Triton X-100 was added to the isopropanol solvent to obtain an impregnation solution. The ITO / Au / Cu 2 The O electrode was immersed in the impregnation solution for 120 s, and the pulling times were 20 times. The interval between each coating was 350 s. After the coating was completed, the electrode was placed in a vacuum drying oven at 45 °C for 7 hours to obtain ITO / Au / Cu 2 O / SnS 2 electrode.
[0099] Step (405): Preparation of NiCoSe x , the same as in Example 1.
[0100] Step (406): NiCoSe x Grind and weigh 5 mg of ground NiCoSe x , added to a mixture of 2.5 ml isopropanol and 5 ml water to obtain a solution containing NiCoSe xThe solution was added with 125 μl of Nafion solution with a mass fraction of 5% to obtain Nafion and NiCoSe x Mix the Nafion and NiCoSe x After the mixed solution was ultrasonically dispersed, it was spin-coated on ITO / Au / Cu 2 O / SnS 2 SnS electrode 2 The surface of the film layer is spin-coated with a hydrogen evolution catalyst NiCoSe x The spin coater was operated at a speed of 2000 rpm to obtain ITO / Au / Cu 2 O / SnS 2 / Nafion / NiCoSe x Electrode, ITO / Au / Cu 2 O / SnS 2 / Nafion / NiCoSe x The electrode was dried in a vacuum oven at 40° C. for 2 hours to obtain a pn heterojunction photocathode material.
[0101] Step (407): The photocathode material is packaged before the photoelectrocatalysis is performed. The packaging is performed by coating the outer edge of the photocathode material with epoxy resin AB glue to prevent the edge Cu 2 O is in contact with the electrolyte.
[0102] The samples obtained in Examples 1 to 4 were characterized and tested for performance, and the results are as follows:
[0103] 1. The deposited Cu 2 The O layer was characterized by using a field emission scanning electron microscope (Hitachi, Japan, model SU-70) to characterize the surface morphology. The characterization results are shown in Figure 3 As shown, Figure 3 A Cu electrodeposition time of different 2 O surface morphology, Figure 3 a is the Cu obtained by electrodeposition for 1 h 2 O surface morphology, Figure 3 b is Cu obtained by electrodeposition for 2 h 2 O surface morphology, Figure 3 c is Cu obtained by electrodeposition for 3 h 2 O surface morphology, Figure 3 d is the Cu obtained by electrodeposition for 6 h 2 O surface morphology. It can be seen from the figure that with the increase of deposition time, Cu 2 O crystal size increased significantly. Combined with the cross-sectional scanning images of samples with different deposition times, the longer the deposition time, the larger the Cu 2The thickness of O is also thicker; as can be seen from the figure, the particle size of the 1h sample is the smallest, the film is uniform and dense, but the film thickness is small, and the number of photogenerated electron holes is limited; the particle size of the 6h sample is already large, close to the micron level, the film surface is rough, and the particle size uniformity is poor; considering the grain size, film thickness and film uniformity, it is considered that 3h deposition is appropriate. The photoelectric performance of the samples under the above different deposition times was tested, and the data showed that the performance was optimal (the photocurrent was the largest) when the electrodeposition time was 3h.
[0104] The Cu in Example 3 was analyzed by Shimadzu XRD-6000 x-ray diffractometer. 2 O was tested by XRD, and blank ITO conductive glass was used as a control. The results are shown in Figure 4 As shown in the figure, there are two XRD diffraction spectra, the lower one corresponds to the blank ITO conductive glass, and the upper one corresponds to the test sample. After deducting the diffraction peak of the ITO blank substrate, it can be seen from the figure that the Cu 2 O diffraction peak, compared with the XRD standard card (PDF 00-005-0667), the diffraction angle of the sample is 29.5°, which corresponds to Cu 2 O crystal (110) plane, 36.6°, 42.5° and 61.4° correspond to Cu 2 O crystal (111), Cu 2 O crystal (200) and Cu 2 O crystal (220) plane. Under this condition, Cu electrodeposited 2 O is mainly cubic crystal and shows a strong (111) orientation.
[0105] 2. For ITO / Au / Cu 2 O electrode for photoelectrocatalytic performance test. The photoelectrocatalytic performance test system is a three-electrode system, ITO / Au / Cu 2 O electrode was used as the working electrode, high-purity graphite rod was used as the counter electrode, saturated calomel electrode was used as the reference electrode, the electrolyte used in the test was 0.1 M sodium sulfate solution, pH = 6.5, the scanning rate of linear voltammetry was 20 mV / s; the scanning range was -1.5 V to 0.25 V (vs. SCE), and the intensity of simulated sunlight was 100 mW / cm 2 The effective area of the sample after packaging is: 0.7~1.0cm 2 The electrolytic cell used is made of high-purity quartz glass. Figure 5 ITO / Au / Cu with different electrodeposition time 2 O electrode photoelectrocatalytic hydrogen evolution performance data diagram. Starting potential (current density J = -0.1mA / cm 2The voltage corresponding to the voltage at 0V (vs.RHE) and the photocurrent (also called short-circuit current) at 0V (vs.RHE) are key parameters for evaluating the performance of photoelectrode materials. Figure 5 It can be seen that the starting potentials of samples at different deposition times are different. The starting potentials of 1h, 2h, 3h and 6h samples are 0.4V, 0.50V, 0.56V and 0.47V (vs. RHE) respectively. The photocurrent (short-circuit current) at 0V (vs. RHE) also has obvious differences. The short-circuit currents of samples at different deposition times are -0.28, -0.45, -1.0 and -0.75mA / cm 2 Obviously, the photoelectrocatalytic hydrogen production performance of the sample deposited for 3h is the best in terms of both open circuit potential and short circuit current. 2 The O electrodeposition time was 3 h.
[0106] The ITO / Au / Cu obtained in Example 3 2 The stability test of O material was carried out by constant potential method. The test equipment was the French Bio-Logic (model VSP) electrochemical workstation, and the light source was the xenon lamp light source (CEL-S500) of Beijing Zhongjiao Jinyuan Technology Co., Ltd. Before the test, the light intensity was calibrated to ensure that the incident light intensity was 100mW / cm 2 The stability test also uses a three-electrode system, with the electrode to be tested as the working electrode, the high-purity graphite rod as the counter electrode, and the saturated calomel electrode as the reference electrode. The electrolyte used in the test is a 0.1M sodium sulfate solution with a pH of 6.5. The electrolytic cell used is made of high-purity quartz glass. Set the test potential (0V vs. RHE) and measure the current change curve over time (It curve).
[0107] The results are as follows Figure 6 As shown in the figure, the current changes with time under constant potential (0Vvs.RHE) under illumination conditions. It can be seen that at the moment of illumination, the cathode current can reach a relatively large value, but it decays quickly. After 200s, the current tends to be flat and at a very small value (about -0.2mA / cm 2 ) current is constant. The main reason is that the unprotected Cu 2 O was directly exposed to the electrolyte and photocorrosion occurred after being irradiated by simulated sunlight.
[0108] 3. For ITO / Au / Cu 2 O / SnS 2 The photoelectric catalytic performance of the electrode was tested. The photoelectric performance test system was the same as the above ITO / Au / Cu 2 The photoelectrocatalytic performance of the O electrode was measured in the same three-electrode system. Figure 8 It can be seen that the number of pulls affects SnS 2The thickness of the film affects the photoelectric response. When the number of pull-ups is 15, the performance is better. The overall current at 0V is lower than that of the pure ITO / Au / Cu 2 O has better performance because Cu 2 O and SnS 2 The formation of a heterojunction is beneficial to the separation of photogenerated electrons and holes and can increase the open circuit voltage to a certain extent, indicating that the heterojunction is effective. Figure 7 It is ITO / Au / Cu in Example 3 2 O / SnS 2 SEM image of the electrode. Figure 7 A is the overall picture, Figure 7 B is a local picture, in which it can be seen that the SnS loaded by the two-step method 2 The film is relatively uniform.
[0109] 4. NiCoSe x It has excellent optical transparency and catalytic activity. It can also protect unstable semiconductors and improve the ability of photocatalytic hydrogen evolution. Fig. 9 It is ITO / Au / Cu in Example 3 2 O / SnS 2 / Nafion / NiCoSe x SEM image of the electrode. Fig. 9 A is the overall picture, Fig. 9 B is a local graph, Fig. 9 It can be seen that NiCoSe x The catalyst particles can be evenly dispersed on the electrode surface.
[0110] The ITO / Au / Cu obtained in Example 3 2 O / SnS 2 / Nafion / NiCoSe x Electrode and ITO / Au / Cu 2 O / SnS 2 / Pt electrode was tested for photoelectric performance using linear voltammetric scanning. The test equipment used was a French Bio-Logic (model VSP) electrochemical workstation, and the light source used was a xenon lamp light source (CEL-S500) from Beijing Zhongjiao Jinyuan Technology Co., Ltd. Before the test, the light intensity was calibrated to ensure that the incident light intensity was 100mW / cm 2 . A three-electrode system was used, with the electrode to be tested as the working electrode, a high-purity graphite rod as the counter electrode, and a saturated calomel electrode as the reference electrode. The electrolyte used in the test was a 0.1M sodium sulfate solution with a pH of 6.5. The electrolytic cell used was made of high-purity quartz glass. The scanning range of the linear voltammetric scan (LSV) was -1.5V to 0.25V (vs. SCE), and the scanning rate was 20mV / s.
[0111] Fig.10 It is the ITO / Au / Cu in Example 3 2 O / SnS 2 / Nafion / NiCoSe x Electrode and ITO / Au / Cu 2 O / SnS 2 / Pt electrode photoelectric performance test comparison chart. Fig.10 It can be seen that compared with the ITO / Au / Cu loaded with precious metal Pt 2 O / SnS 2 / Pt electrode, ITO / Au / Cu 2 O / SnS 2 / Nafion / NiCoSe x The photoelectrocatalytic performance is significantly improved, and the current can reach -3.9mA / cm at 0V (vs RHE) 2 , and the open circuit voltage can reach 0.5V. At the same time, ITO / Au / Cu 2 O / SnS 2 The open circuit voltage of the ITO / Au / Cu / Pt electrode can reach 0.61V, which shows the effectiveness of the heterojunction. 2 O electrode, ITO / Au / Cu 2 O / SnS 2 / Nafion / NiCoSe x Electrode stability is also greatly improved.
[0112] The ITO / Au / Cu obtained in Example 3 2 O / SnS 2 / Nafion / NiCoSe x The electrode was tested for constant potential stability under illumination conditions using a constant potential method. The test equipment used was a French Bio-Logic (model VSP) electrochemical workstation, and the light source used was a xenon lamp light source (CEL-S500) from Beijing Zhongjiao Jinyuan Technology Co., Ltd. Before the test, the light intensity was calibrated to ensure that the incident light intensity was 100mW / cm 2 The stability test also uses a three-electrode system, with the electrode to be tested as the working electrode, the high-purity graphite rod as the counter electrode, and the saturated calomel electrode as the reference electrode. The electrolyte used in the test is a 0.1M sodium sulfate solution with a pH of 6.5. The electrolytic cell used is made of high-purity quartz glass. Set the test potential (0V vs. RHE) and measure the current change curve over time (It curve).
[0113] Fig.11 It is the ITO / Au / Cu of Example 3 2 O / SnS2 / Nafion / NiCoSe x Electrode constant potential stability test diagram. It can be seen from the figure that ITO / Au / Cu 2 O / SnS 2 / Nafion / NiCoSe x The electrode can be at -0.75mA / cm 2 The current is kept constant for more than 15 minutes. 2 O electrode, ITO / Au / Cu 2 O / SnS 2 / Nafion / NiCoSe x The current stability and current density of the electrode are improved, on the one hand, due to the SnS 2 With Cu 2 O forms a heterojunction, which can promote the separation of photogenerated electrons and holes; on the other hand, NiCoSe x Hydrogen evolution catalysts can accelerate the consumption of photogenerated electrons. Fig.12 It is the ITO / Au / Cu in Example 3 2 O / SnS 2 / Nafion / NiCoSe x Electrode stability test chart. From the chart, we can see that the light source is turned on and off at intervals to observe the light response state of the electrode. The photocurrent in the on state is large, and the current in the off state is small. 2 The photoresponse becomes weaker due to the continuous photocorrosion of O.
[0114] in addition, Fig.14 ITO / Au / Cu 2 Cross-sectional scanning photo of the O electrode, with a uniform and dense layer in the middle and a 100nm thick Au layer. 2 The thickness of the O sample is about 1.5 μm. 2 The thickness of the O sample is about 2.5 μm.
[0115] It is worth noting that the pn heterojunction photocathode material in the present invention comprises: a base layer, on which Au layer, Cu layer and Cu layer are sequentially attached from bottom to top. 2 O thin film layer, SnS 2 The surface of the perfluorosulfonic acid polymer film layer is loaded with a hydrogen evolution catalyst NiCoSe x , through Cu 2 SnS is loaded on the surface of O thin film layer 2 The thin film layer makes Cu 2 O and SnS 2 The formation of a heterojunction is beneficial to the separation of photogenerated electrons and holes, increasing the open circuit voltage, and2 Stable and dense perfluorosulfonic acid polymer film layer is formed on the surface and high-efficiency hydrogen evolution catalyst NiCoSe is loaded x , which helps to reduce the recombination rate of photogenerated electrons and holes, improve the efficiency of photoelectrocatalytic hydrogen evolution, and protect the electrode to improve stability. In addition, the prior art uses the ALD (atomic layer deposition) method to deposit Cu 2 The surface of O is loaded with ZnO, or ZnO doped with Al, i.e., AZO. In the present invention, ZnO or AZO is replaced by SnS 2 Instead, the immersion pulling method is used, which does not require expensive ALD equipment and saves costs.
[0116] The serial numbers of the above embodiments of the present invention are only for description and do not represent the advantages or disadvantages of the embodiments.
[0117] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A pn heterojunction photocathode material, characterized in that: The photocathode material is layered and includes: a substrate layer; The base layer is provided with an Au layer, a Cu2O thin film layer, a SnS2 thin film layer and a perfluorosulfonic acid polymer thin film layer in sequence from bottom to top; The surface of the perfluorosulfonic acid polymer film layer is loaded with a hydrogen evolution catalyst; The hydrogen evolution catalyst is NiCoSe x ; The thickness of the Au layer is 100 to 200 mm; The thickness of the Cu2O thin film layer is 1.5 to 2.5 μm; The base layer is an ITO conductive glass layer; In the Cu2O thin film layer, the microscopic crystal morphology of Cu2O is cubic crystal, and the Cu2O thin film layer as a whole is a dense and uneven micro-nano cone array thin film.
2. The method for preparing a pn heterojunction photocathode material according to claim 1, characterized in that: The method comprises: Plating an Au layer on the surface of the substrate layer to obtain a substrate layer / Au material; Growing a Cu2O thin film layer on the surface of the Au layer to obtain a base layer base layer / Au / Cu2O material; A SnS2 thin film layer is loaded on the surface of the Cu2O thin film layer to obtain a base layer / Au / Cu2O / SnS2 material; The surface of the SnS2 thin film layer is spin-coated with a hydrogen evolution catalyst NiCoSe x The perfluorosulfonic acid polymer thin film layer is formed to obtain the pn heterojunction photocathode material.
3. The method for preparing a pn heterojunction photocathode material according to claim 2, characterized in that: The method for growing a Cu2O thin film layer on the surface of the Au layer comprises: The base layer plated with the Au layer is used as a working electrode, the working electrode is immersed in an electrolyte, a high-purity carbon rod is used as a counter electrode, Hg / HgO is used as a reference electrode, and the Cu2O thin film layer is grown on the surface of the Au layer by electrodeposition to obtain the base layer / Au / Cu2O material.
4. The method for preparing a pn heterojunction photocathode material according to claim 3, characterized in that: The electrodeposition conditions are: The electrodeposition current density is -0.1~-0.2mA / cm 2 , the electrodeposition time is 1-6 hours, and the electrodeposition temperature is 30-50°C; The components of the electrodeposition electrolyte at least include: 0.8-1.2 mol / L of copper sulfate pentahydrate, 0.4-0.6 mol / L of sodium lactate, and 0.08-0.12 mol / L of Triton X-1000; The electrodeposition electrolyte also includes a surfactant, and the amount of the surfactant added is 0.8-1.2% of the volume of the electrodeposition electrolyte; The surfactant is polyethylene glycol PEG-200; The pH of the electrodeposition electrolyte is 11 to 12; The electrodeposition electrolyte also includes a pH regulator, which is an alkaline substance; The alkaline substance is selected from at least one of NaOH and KOH.
5. The method for preparing a pn heterojunction photocathode material according to claim 2, characterized in that: The method for loading a SnS2 thin film layer on the surface of the Cu2O thin film layer comprises: SnS2 nanoparticles are ground and ultrasonically dispersed in solvent A to obtain an impregnation solution, wherein Triton X-100 is added to the solvent A. The base layer / Au / Cu2O material is immersed in the impregnation solution by using the immersion pulling method, and the SnS2 thin film layer is loaded on the surface of the Cu2O thin film layer. After the loading is completed, it is dried to obtain the base layer / Au / Cu2O / SnS2 material.
6. The method for preparing a pn heterojunction photocathode material according to claim 5, characterized in that: In the impregnation solution, the volume of the Triton X-100 is 1-2% of the volume of the solvent A; the mass volume ratio of the SnS2 nanoparticles to the solvent A is 1:2-3; The solvent A is selected from at least one of ethanol and isopropanol; The conditions of the immersion pulling method are: the immersion time is 30-120s, the pulling times are 5-20 times, and the interval time between each time is 250-350s; The drying conditions are as follows: drying temperature is 35-45° C., and drying time is 5-7 hours.
7. The method for preparing a pn heterojunction photocathode material according to claim 2, characterized in that: The surface of the SnS2 thin film layer is spin-coated with a hydrogen evolution catalyst NiCoSe x The method of forming a perfluorosulfonic acid polymer film layer comprises: Containing NiCoSe x The solution is mixed with the solution containing Nafion to obtain Nafion and NiCoSe x Mixed liquid, The Nafion and NiCoSe x After the mixed solution is ultrasonically dispersed, it is spin-coated on the surface of the SnS2 thin film layer of the substrate layer / Au / Cu2O / SnS2 material and dried to obtain the pn heterojunction photocathode material.
8. The method for preparing a pn heterojunction photocathode material according to claim 7, characterized in that: The NiCoSe x The solution further includes a solvent B, wherein the solvent B is a mixture of water and isopropanol, The volume ratio of the water to the isopropanol is 4-2:1; The NiCoSe x NiCoSe in solution x The mass ratio of the Nafion-containing solution to the isopropanol is 1:200-400, the mass fraction of Nafion in the Nafion-containing solution is 5%, and the volume ratio of the Nafion-containing solution to the isopropanol is 0.05:
1.
9. The method for preparing a pn heterojunction photocathode material according to claim 7, characterized in that: The drying conditions are as follows: drying temperature is 35-45° C., and drying time is 1-3 hours.
Citation Information
Patent Citations
Tin sulfide film solar battery
CN101378090A
Zinc oxide based solar battery and preparation method thereof
CN101615640A